2010
DOI: 10.1017/s1138741600002328
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Teachers' Psychological Distress through a Mindfulness Training Program

Abstract: Teachers constitute one of the professional collectives most affected by psychological problems. The purpose of this quasi-experimental study is to examine the efficacy of a mindfulness training programme to reduce psychological distress in a group of teachers. The sample comprised 68 teachers of Secondary School Education, from various public schools; half of them formed the experimental group, and the another half the control group. The levels of psychological distress were measured, in both groups, by the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 40 publications
4
50
0
8
Order By: Relevance
“…Second, teachers in the intervention group participated in mindfulness training as part of a one-day teacher training workshop. Recent studies have shown that teachers who practice mindfulness experience reductions in psychological symptoms, occupational stress, and burnout as well as increases in focused attention, working memory, and self-compassion (Franco, Mañas, Cangas, Moreno, and Gallego, 2010; Gold et al, 2010, Jennings, Snowberg, Coccia, & Greenberg, 2011, Roeser et al, 2012). In the current study, although the teacher training workshop was only one day, it is possible that learning mindfulness influenced teachers’ behavior, in general.…”
Section: Discussionmentioning
confidence: 99%
“…Second, teachers in the intervention group participated in mindfulness training as part of a one-day teacher training workshop. Recent studies have shown that teachers who practice mindfulness experience reductions in psychological symptoms, occupational stress, and burnout as well as increases in focused attention, working memory, and self-compassion (Franco, Mañas, Cangas, Moreno, and Gallego, 2010; Gold et al, 2010, Jennings, Snowberg, Coccia, & Greenberg, 2011, Roeser et al, 2012). In the current study, although the teacher training workshop was only one day, it is possible that learning mindfulness influenced teachers’ behavior, in general.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands almost one in five teachers suffers from burnout complaints, compared to one in eight employees in the general working population [4]. Most of the interventions to prevent work-related stress in education aim to increase the resources of the individual to deal with the demands of the job [510]. However, these interventions were only partially effective in influencing (dimensions of) burnout [57, 9, 10] and well-being [10].…”
Section: Introductionmentioning
confidence: 99%
“…Los hallazgos obtenidos en diversos estudios han demostrado que la práctica regular y continua de la meditación produce diferentes efectos beneficiosos sobre el organismo, algunos de ellos relacionados con la ansiedad (Solberg, Ingjer, Holen, Sundgot-Borgen, Nilsson y Holme, 2000), reducción de la tensión arterial (Barnes, Treiber y Davis, 2001), mejora significativa del insomnio (Jacobs, Benson y Friedman, 1993), reducciones de los niveles de nerviosismo, preocupación, malestar emocional y estrés e incrementos de los niveles de relajación muscular, tranquilidad emocional y del grado de bienestar general Franco, Mañas, Cangas, Moreno y Gallego, 2010), entre otros.Por todo ello, se han desarrollado intervenciones basadas en mindfulness para tratar trastornos específicos como depresión, adicciones, trastornos de la conducta alimentaria, trastornos de ansiedad, trastornos relacionados con el dolor corporal y la salud en general (Orsillo, Roemer, Block, Lejeune y Herbert, 2004;Orsillo, Roemer, BlockLerner y Tull, 2004, Franco, Mañas y Justo 2010. Los datos preliminares de investigaciones con estas técnicas han aportado cierta evidencia en apoyo de esos tratamientos (Baer, 2003;.…”
Section: Introductionunclassified